Lecturer Professional Development Strategies in a Higher Education Institution in Ha Tinh Province at a Time of Educational Reforms - TranHai Ngoc; PhanVan Nhan; DoanHoai Son; TranThi Ai Duc; TranGiang Nam (Voprosy obrazovaniya / Educational Studies Moscow, 2020)
Lecturer professional development (LPD) plays a significant role in enhancing student achievement and school improvement. It is a process which starts during lecturer training at tertiary education institutions and extends to include job-embedded and collaborative professional learning opportunities for lecturers at their institutions. Many strategies for lecturer professional development have been proposed in the literature on higher education. This qualitative case study investigation sought to identify various typical strategies employed to promote lecturer professional development at Ha Tinh University in Central Vietnam. Ten strategies were identified, some of which were university-based, while others were offered externally. These strategies are described within the context of significant reforms being implemented in the higher education sector in Vietnam.